Tonia and Her Children - Łoziński, Marcel 1940-; Kowalczyk, Magda 1983-; Łoziński, Paweł 1965-; Petrycki, Jacek 1948- (DOX, 2012)
Wrocław, 1949. Tonia, a prewar communist activist and the mother of two children, is arrested and sentenced to five and a half years’ imprisonment for collaboration with the American intelligence services. From that moment her children became wards of the state and were raised in various orphanages. Werka and Marcel pay a high price for their parents’ views and ideals. Stigmatized for life they attempt to find a place for themselves in a new reality. Today over 70 years old, Werka and Marcel talk about their painful and difficult experiences from childhood. A moving, highly emotive film. [www.topdocfilm.com]